Integration of Islamic Psychotherapy and Self-Disclosure Methods for Mitigating Adolescent Suicidal Ideation: A Madrasah Study - syafii, Hisyam (PT Ilmu Inovasi Nusantara, 2024)
This study addresses the rising concern of suicidal ideation among adolescents within Islamic educational institutions, emphasizing the need for culturally and spiritually sensitive interventions. The primary aim of this research is to explore and evaluate the integration of Islamic psychotherapy and self-disclosure methods as a comprehensive approach to support the mental health of madrasa students. This integrative framework incorporates Islamic values ​​such as husnudzon (positive thinking), patience (resilience), and tawakkal (trust in God) with structured self-disclosure, enabling students to express personal thoughts and emotions in a safe environment. Using a Systematic Literature Review (SLR) approach, the study reviews academic sources from databases such as Scopus, Web of Science, and Index Islamicus to gather insights on Islamic-based psychotherapeutic methods and self-disclosure in addressing suicidal ideation among adolescents. Findings indicate that combining Islamic spiritual values ​​with modern therapeutic techniques offers a unique and effective approach for reducing psychological distress, enhancing emotional regulation, and fostering spiritual resilience among adolescents. This study contributes to the growing field of Islamic psychology by providing a dual framework for preventive and curative interventions tailored to the needs of madrasa students. Practical implications include designing culturally relevant mental health programs in religious educational settings.